Aleutians -- lessons from a forgotten campaign. - Huntoon, David H., Jr. (Fort Leavenworth, KS : US Army Command and General Staff College, 1988)
This monograph analyzes the campaign in the Aleutians of 1943 in which Japanese and U.S. forces struggled violently for strategic control of austere ground in what has been aptly called the "forgotten war". Several theoretical concepts are tested against the backdrop of the Aleutian campaign. These are the role of leadership and command and control, the perils of conducting ad hoc joint operations, and the critical linkages between the tactical, operational and strategic levels of war. The Aleutian campaign offers significant insights as one of the first joint amphibious operations of the Second World War in a misunderstood and relatively unknown theater. This campaign reflected planning errors which led to disastrous operational results. Both the Japanese and American sides are analyzed to understand the campaign process from planning to execution to end state. The theoretical concepts are then examined in greater depth with conclusions for the use and misuse of theory. The operational planner of the 1990's is cautioned about the unique nature of the Aleutians (and all historical examples) by a strong reference to context. If lessons of history can be learned with theoretical and practical value to the reader then the monograph will have served its purpose in this study of an extraordinary American campaign. It is argued that the geographical isolation, interservice miscommunications, strategic, operational, and tactical linkage failures, and the element of unpreparedness which marked the Aleutians will probably be revisited by the American military in the next several decades.